Medical Student Musculoskeletal Knowledge: Examining the Impact and Value of an Orthopaedic Surgery Clerkship Using the Freedman and Bernstein Examination - Nicole Nishime; Mary Seibel; Dieter Lindskog; Daniel Wiznia (BMC Medical Education)
Abstract Purpose Given the importance of musculoskeletal knowledge but the limited orthopaedic instruction offered in medical school, our Orthopaedic Surgery Department developed a three-week clerkship for interested students. This study assesses the clerkship’s impact on medical student musculoskeletal knowledge through administration of the Freedman and Bernstein Basic Cognitive Musculoskeletal Examination. Methods Medical students enrolled in the orthopaedic surgery clerkship between February 2019 and May 2024 were asked to participate in pre- and post-clerkship surveys using the Freedman and Bernstein Basic Cognitive Musculoskeletal Examination. Raw and weighted scores were computed according to the guidelines provided by Freedman and Bernstein. Averaged scores were used to compute mean pre- and post-test scores. Results There were 64 responses to the pre-test and 33 responses to the post-test. The mean pre-test weighted score was 54% with 12 students (18.8%) passing. The mean post-test score was 70% with 17 students (51.5%) passing. Raw scores showed that musculoskeletal knowledge improved from pre-test (M = 55.13, SD = 19.90) to post-test (M = 70.22, SD = 14.70; p < .001). The results comparing weighted scores showed that the participants’ musculoskeletal knowledge also improved from pre-test (M = 52.86, SD = 21.12) to post-test (M = 67.11, SD = 19.02; p < .001). Conclusion While students demonstrated improved musculoskeletal knowledge after completing our institution’s orthopaedic surgery clerkship, almost half of the students did not pass the post-test. Most of the students who did not pass the post-test expressed definite or possible interest in pursuing an orthopaedic surgery residency.